2008
DOI: 10.1001/archderm.144.9.1228
|View full text |Cite
|
Sign up to set email alerts
|

New Contrast Stain for the Rapid Diagnosis of Dermatophytic and Candidal Dermatomycoses

Abstract: R apid diagnosis of superficial dermatomycoses is important so that treatment can be initiated without delay. We compared a new contrast stain with the routine test of potassium hydroxide (KOH) wet mount and culture for the diagnosis of dermatophytic and candidal dermatomycoses.Methods. Skin scrapings were taken from outpatients with superficial dermatomycoses and cultured in Sabouraud dextrose agar with cycloheximide. They were then evaluated under a microscope using both the KOH wet mount technique and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 5 publications
0
14
1
2
Order By: Relevance
“…The low specificity of both CW and CSB stains can be attributed to inability of the KOH test itself to detect true positives. Even in experienced hands, the false positive and false negative rates of KOH have been reported as 14% and 5–25%, respectively . However, when availability, ease of detection, and cost‐effectiveness were considered, CSB was found to be better than CW in the diagnosis of dermatophytoses.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…The low specificity of both CW and CSB stains can be attributed to inability of the KOH test itself to detect true positives. Even in experienced hands, the false positive and false negative rates of KOH have been reported as 14% and 5–25%, respectively . However, when availability, ease of detection, and cost‐effectiveness were considered, CSB was found to be better than CW in the diagnosis of dermatophytoses.…”
Section: Discussioncontrasting
confidence: 69%
“…However, they are technically demanding, require up to 48 hours to complete, and will not be available in laboratories in developing countries for the foreseeable future. In contrast to other studies (Table ), our study compared all the three methods at the end of 5 and 30 minutes and hence demonstrated that the CSB stain is a better stain for the rapid diagnosis of dermatophytoses because of ease of performance and differentiation of artifacts, rapidity of detection, better appreciation of morphology of fungal elements, and cost effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two other dyes available are Chicago blue 6,7 and chlorazole black. 4 The aim of this study is to compare Chicago blue-KOH and chlorazole black-KOH stains with the Parker ink-KOH stain and with culture, which in this study is considered the diagnostic gold standard.…”
Section: Introductionmentioning
confidence: 99%